An Analysis of German-Language Media Texts on Topics Involving School and University - Levitskaya, Anastasia; Seliverstova, Lyudmila (Communication Today, 2025)
The study offers a hermeneutic analysis of German-language media texts on topics regarding schools and students (German films and media contents published on websites of general interest, on news portals and in specialised online magazines, as well as on Internet portals specifically intended for teachers and teachers’ personal blogs). These media texts were examined in terms of representation of image of the main participants in the educational process – the teacher and the student, as well as the educational institution as a whole – school and/or university. The analysis indicates a change in the educational paradigm in (late) modern Germany, which leads to a change in the roles of participants in the educational process, as reflected in media texts of all genres and forms, including those published on the Internet. The modern teacher is assigned the role of a facilitator, consultant and moderator, who accompanies and guides the student, but not a leader who students follow, as it used to be earlier. A common set of topical issues in the field of education is discussed in relation to the German-speaking cinema and the Internet space. However, media form predominantly negative content with regard to teachers and school education; specialised magazines focused on a certain circle of readers (parents, teachers, etc.) mainly discuss the positive aspects of the learning process; teachers in their blogs discuss the current issues, sharing experiences and effective work practices with their students.